THE AFRIKANDER VOLUNTEER CORPS AND THE PARTICIPATION OF AFRIKANERS IN CONFLICTS IN RHODESIA, 1893–1897 - Hendrich, Gustav (Scientia Militaria - South African Journal of Military Studies, 2012)
During the last decade of the nineteenth century, British colonisation in Southern Africa, in particular in Rhodesia (today Zimbabwe) had coincided with uneasy relations with the native black population. Partly because of continuing disillusionment over stringent policy regarding native livestock, hostilities between the colonial officials and Matabele and Mashona tribal groups resulted in devastating wars. Within these warring circumstances, Afrikaner settlers who had immigrated to Rhodesia since 1891 – mostly in search of better living opportunities – subsequently found themselves amidst the crossfire of these conflicts. Though subjugated to British colonial authority, the Afrikaner minority were regarded by native blacks as collaborators in maintaining white military and political power in Rhodesia. Consequently, the mere safety of Afrikaners were threatened by sporadic military attacks and skirmishes during the Anglo-Matabele war of 1893, and most of all, for the duration of the Matabele and Mashona rebellions of 1896 to 1897. During the Matabele rebellion, an Afrikander Volunteer Corps (known as the Afrikaner Korps) was established as a military unit, which provided substantial support in two decisive battles. This article seeks to address the role and history of the Afrikander Volunteer Corps, as well as the involvement of ordinary Afrikaners in the turbulent colonial wars in early Rhodesia.